Physiological and biochemical responses of Isatis indigotica to deficit irrigation in a cold and arid environment - Zhou, Chenli; Yu, Shouchao; Zhang, Hengjia; Li, Fuqiang (Frontiers in Plant Science, 2023)
Water shortage and wastage are critical challenges to sustainable agricultural development, especially in arid and semiarid regions worldwide. Isatis indigotica (woad), as a traditional Chinese herb, was planted in a large area in a cold and arid environment of Hexi. Regulated deficit irrigation can reduce the growth of some vegetative organs by changing the accumulation and distribution of photosynthetic products in crops, thus increasing the economic yield of crops. In agricultural production, crop productivity may be improved by mulched drip irrigation and deficit irrigation. Hence, a field experiment was conducted to investigate the responses of photosynthesis, malondialdehyde, osmotic regulators, antioxidant enzyme activities, and the yield of woad to water deficit at different growth stages. The growth stage of woad was divided in four stages: seedling, vegetative growth, fleshy root growth, and fleshy root maturity. During vegetative growth, fleshy root growth, and fleshy root maturity, three water gradients were set for plants with mild (65–75% in field water capacity, FC), moderate (55–65% in FC), and severe (45–55% in FC) deficits, respectively. In contrast, an adequate water supply (75–85% in FC) during the growth period was designed as the control (CK). The net photosynthetic rate (Pn), transpiration rate, and stomatal conductance of woad significantly decreased (P < 0.05) by moderate and severe water deficits. Still, rehydration after the water deficit could produce a noticeable compensation effect. In contrast, malondialdehyde and proline accumulation significantly increased under moderate and severe water deficits. At the same time, the superoxide dismutase, peroxidase, and catalase all had high activities (increased significantly by 19.87–39.28%, 19.91–34.26%, and 10.63–16.13% compared with CK, respectively), but yields were substantially lower, compared to CK. Additionally, the net photosynthetic rate was negatively correlated with antioxidant enzyme activity. The economic yield of plants subjected to continuous mild water deficit during both vegetative and fleshy root growth was not significantly different from that in CK. Still, the water use efficiency improved significantly. Therefore, the continuous mild water deficit during vegetative and fleshy root growth could improve the physiological and biochemical mechanisms of the plant, representing an optimal irrigation strategy for woad in cold and arid areas.